Pemanfaatan ArcGis dalam Analisis Pola Pergerakan dan Rute Baru di Kota X - Zia Felina; Andriani Effendi; Emil Padila (LPPM Universitas Abdurrab, 2025)
Transportation supports regional growth and improves accessibility. A more efficient new route plan is needed in City X because population and business growth are not balanced with an adequate network of routes. The minibus (Elf) is chosen because it is easy to operate and can reach local corridors. By using ArcGIS, the Geographic Information System (GIS) is used in this study to analyze the road network, settlement patterns, activity centers, and community travel needs. The results of the analysis produce alternative routes that are more efficient and aligned with the movement patterns of the residents. It is expected that these routes will improve public transportation services in City X and support sustainable transportation policies.